Risk factors for anaemia among Ghanaian women and children vary by population group and climate zone. Issue 2 (18th September 2020) - Petry, Nicolai; Wirth, James P.; Adu‐Afarwuah, Seth; Wegmuller, Rita; Woodruff, Bradley A.; Tanumihardjo, Sherry A.; Bentil, Helena; Donkor, William E.S.; Williams, Thomas N.; Shahab‐Ferdows, Setareh; Selenje, Lilian; Mahama, Abraham; et al.
Abstract: Anaemia has serious effects on human health and has multifactorial aetiologies. This study aimed to determine putative risk factors for anaemia in children 6–59 months and 15‐ to 49‐year‐old non‐pregnant women living in Ghana. Data from a nationally representative cross‐sectional survey were analysed for associations between anaemia and various anaemia risk factors. National and stratum‐specific multivariable regressions were constructed separately for children and women to calculate the adjusted prevalence ratio (aPR) for anaemia of variables found to be statistically significantly associated with anaemia in bivariate analysis. Nationally, the aPR for anaemia was greater in children with iron deficiency (ID; aPR 2.20; 95% confidence interval [CI]: 1.88, 2.59), malaria parasitaemia (aPR 1.96; 95% CI: 1.65, 2.32), inflammation (aPR 1.26; 95% CI: 1.08, 1.46), vitamin A deficiency (VAD; aPR 1.38; 95% CI: 1.19, 1.60) and stunting (aPR 1.26; 95% CI: 1.09, 1.46). In women, ID (aPR 4.33; 95% CI: 3.42, 5.49), VAD (aPR 1.61; 95% CI: 1.24, 2.09) and inflammation (aPR 1.59; 95% CI: 1.20, 2.11) were associated with anaemia, whereas overweight and obese women had lower prevalence of anaemia (aPR 0.74; 95% CI: 0.56, 0.97). ID was associated with child anaemia in the Northern and Middle belts, but not in the Southern Belt; conversely, inflammation was associated with anaemia in both children and women in the Southern and Middle belts, but not in the Northern Belt. Anaemia control programmes should be region specific and aim at the prevention of ID, malaria and other drivers of inflammation as they are the main predictors of anaemia in Ghanaian children and women.